2007
DOI: 10.1002/cm.20206
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila nucleoporin gene nup154 is required for correct microfilament dynamics and cell death during oogenesis

Abstract: The Drosophila nucleoporin gene nup154 is required in both male and female germline for successful gametogenesis. Mutant flies lack differentiated sperm and lay abnormal eggs. We demonstrated that the egg phenotype was associated with specific alterations of the actin cytoskeleton at different stages of oogenesis. Actually, mutant egg chambers displayed an abnormal organization of both subcortical microfilaments and cytoplasmic actin bundles, that led to defective nurse cell dumping. TUNEL analysis also showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…It is suggested that the differences in the level of CI decline with age are due to the density of Wolbachia, particularly in the sperm cysts in the testes, with higher densities resulting in higher severity of CI expression (Boyle et al ., ; Breeuwer & Werren, ; Giordano et al ., ; Mercot et al ., ; Bourtzis et al ., , ; Poinsot et al ., ; Rousset et al ., ; Veneti et al ., ). This suggestion is corroborated by the observation that Wolbachia density decreases within male germ cells with the onset of male age in D. simulans (Riparbelli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is suggested that the differences in the level of CI decline with age are due to the density of Wolbachia, particularly in the sperm cysts in the testes, with higher densities resulting in higher severity of CI expression (Boyle et al ., ; Breeuwer & Werren, ; Giordano et al ., ; Mercot et al ., ; Bourtzis et al ., , ; Poinsot et al ., ; Rousset et al ., ; Veneti et al ., ). This suggestion is corroborated by the observation that Wolbachia density decreases within male germ cells with the onset of male age in D. simulans (Riparbelli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Studies on hypomorphic mutant alleles of Nup154 in Drosophila demonstrated that Nup154 in males is required for testicular cyst formation, control of spermatocyte proliferation, and meiotic progression (27). In Drosophila females, Nup154 is essential for egg chamber development and oocyte growth (27,46,47). Interestingly, in mutant egg chambers, the Nup154 protein accumulated in the cytoplasm, while it was only barely detected at its usual functional location in the nuclear envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the oogenesis defects produced by the weak egg alleles show that Egg is required for at least two late events in oogenesis: nurse cell dumping and formation of the eggshell and its structures. The presence of persistent nurse cells associated with mature stage 14 oocytes may also indicate a unique role of H3K9 methylation in the programmed death of nurse cells in late oogenesis (Pritchett et al, 2009), or nurse cell death could be delayed as a consequence of defects in nurse cell dumping (Foley and Cooley, 1998; Riparbelli et al, 2007). Future studies in our lab will address whether H3K9me promotes specific changes in chromatin structure that accompany these terminal events in oogenesis, or if its primary function is to regulate the expression of genes required for these events.…”
Section: Discussionmentioning
confidence: 99%